Pharmaceutical regulation at the wholesale level and parallel trade - Laura Birg (University of Göttingen, Center for European, Governance and Economic Development Research (cege), 2013)
This paper studies the effect of pharmaceutical regulation at the wholesale level, if markets are integrated by parallel trade, i.e. trade outside the manufacturers authorized distribution channel. In particular, maximum wholesale margins, a restriction of pricing by the intermediary, and mandatory rebates, a restriction of the pricing by the manufacturer, are analyzed with respect to their effect on drug prices, quantities, and public pharmaceutical expenditure. Maximum wholesale margins enhance the manufacturers ability to reduce competition from parallel trade in the destination country by increasing wholesale prices. In a symmetric equilibrium, maximum wholesale margins of both countries partly offset each other. Mandatory rebates may be a policy alternative, as they exhibit a reinforcing effect with respect to drug prices.
Keywords: F12; I11; I18; 330; parallel trade; regulation; maximum markups; spillovers; mandatory rebates